The Great Game : Secret Service in High Asia - Hopkirk, Peter (Lahore Combine Printers, 1994)
The Great Game, a deadly struggle in the last century between secret agents of the two superpowers--Victorian Britain and Tsarist Russia--has once again become ominously topical, as a new power struggle begins in Central Asia.
Include Maps and Index
Keywords: Great Britain -- Soviet Union -- Politics and government